Pengaruh kepimpinan ‘ubudiyyah , mas’uliyyah dan itqan terhadap pengurusan konflik dan kualiti guru Sekolah Menengah Yayasan Islam Kelantan - Zawawi, Zakaria (2021)
The leadership practice of Yayasan Islam Kelantan (YIK) teachers is still stuck with the idealism of western leadership practice which is seen as less focused on the philosophy of Islamic education is an issue that needs to be addressed. This study aims to examine the influence of Ubudiyyah, Mas’uliyyah, and Itqan (UMI) leadership practices on conflict management and teacher quality in YIK schools. The design of this quantitative study was implemented on 350 YIK teachers selected as a sample through a cross-sectional survey method using UMI instruments (Kelantan Institute of Teacher Training, ROCKY II conflict management practices and instruments teacher quality. The finding of study found that UMI's leadership practices, conflict management practices, and the quality of YIK teachers are at a high level. However, there are differences in UMI leadership practices, conflict management practices, and teacher quality among YIK teachers. The findings also show that there is a significant relationship in UMI leadership practices with conflict management practices and the quality of YIK teachers. UMI's leadership practices were found to have an influence on conflict management practices and the quality of YIK teachers. Therefore, the findings of the study show the importance of improving the achievement of schools in YIK through the empowerment of UMI leadership, conflict management, and teacher quality. Therefore, the YIK and the Kelantan state government need to take action to improve the quality of teachers by ensuring that the achievement of excellence in YIK schools can be increased through strengthening training in UMI leadership practices and conflict management practices among YIK teachers.